Canadian fellowship experience: the different challenges and emotions faced by an International Medical Graduate and mitigation strategies - Belfiore, Elio BR; Zasso, Fabricio; Santos, Filipe NC (Canadian Medical Education Journal, 2022)
Acknowledging the mental remodeling that a foreign physician goes through and attempting to mitigate the difficulties of this process is crucial to achieving better outcomes in education and patient care. Canada's Healthcare System offers Clinical Fellowship Programs that allow physicians specialists to obtain advanced expertise in a chosen subspecialty. In a Clinical Fellowship, Canadian Medical Graduates (CMGs) practice alongside International Medical Graduates (IMGs); however, there is evidence that they undergo different challenges in the learning experience. IMGs usually have a higher cognitive load during the adaptation period, which can be due to multiple factors, such as the transition to practice in a foreign country, language, level of supervision, teaching methods applied, feeling disconnected from home, and other competing needs fellows face outside of the clinical context. We propose strategies that may help mitigate the transition to practice process that IMGs undergo when starting a Canadian fellowship, such as Self-Efficacy Encouraging Approach, Thinking Framework Across Cultures, and Social Engagement and Wellbeing.